A Decision Support System for Rice Cultivation on Acid Sulfate Soils in Malaysia - Totok Suswanto; Shamshuddin Jusop; S.R. Syed Omar; C.B.S. The; Peli Mat (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2005)
Ameliorative steps to put acid sulfate soils into productive use can be organized by a decision support system. The model uses microeconomic analysis to get an optimal rate of lime and fertilizer in maximizing profit. A glasshouse experiment was conducted on an acid sulfate soil in Malaysia to get the potential yield. A field trial was conducted for validation purposes. The recommended rate of fertilizer application of 150-200 kg ha-1 N. 20-30 kg ha-1 P and 150-200 kg ha-1 K were applied during the critical stage of the rice growth. Field Adjusting Factor (FAF) of 0.40 has been found and this was used to analyze the production function. Using TableCurve 3D software. an equation for production function was established. Validation using experimental data showed that the equation has a good capability. shown by the value of p>0.2 (t-test) and MEE of 2%. The model. named as RiCASS (Rice Cultivation on Acid Sulfate Soil) was developed and successfully simulatedthe maximal profit under 4 different scenarios. The recommended rate of lime (GML) was 6.5 t ha-1 for maximal profit and 2.5- 3.0 t ha-1 for the farmers, practice. Keywords: Acid sulfate soil. decision support system. field adjusting factor. lime. rice